Measures of association in epidemiological studies: smoking mothers and low birth weight children in the city of Campina Grande – PB - Albuquerque, Tarsyla Medeiros de; Araujo, Gabriela Albuquerque Batista de; Caminha, Bruno Leão; Albuquerque, Marta Lucia de; Albuquerque, Mácio Augusto de (Acta Scientiarum. Health Sciences, 2016)
The aim of this study was to present and describe the essential aspects, and to discuss the use of measures of association, relative risk and odds ratio, including formulas for calculating confidence intervals of obtained data from a cohort study of underweight live births of mothers who smoked during pregnancy, whose deliveries were performed in hospitals and maternity wards located in Campina Grande, state Pernambuco. Smoking during pregnancy was analyzed as a potential risk factor for low birth weight among 3612 newborns. In assessing the association of outcome, there were no large numeric differences between the estimates of the relative risk, odds ratios and confidence intervals obtained. It is an acceptable approximation to the relative risk and the odds ratio. It is up to the researcher to choose the most appropriate technique to its subject matter and should be determined according to the surveyed data.